Pengaruh kompetensi karyawan dan manajemen talenta terhadap kinerja karyawan pada UMKM di Kota Bandung - Istikomah, Istikomah; Hartiati, Leni; Dzulfiqar, Irfan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Faster developments, more open global competition, and increasingly advanced technology require a company to have a competitive advantage. This study aims to determine the effect of employee competence and talent management on employee performance in the context of MSMEs in Bandung City. This study uses a descriptive verification approach. The collected data were then analyzed using multiple regression analysis with the help of SPSS 25 for Windows software. The results of this study contribute to the following findings: First, employee competence was found to have a positive influence on the performance of MSME employees in the city of Bandung. Second, talent management also has a positive influence on the performance of MSME employees in the city of Bandung. And finally, this study also proves simultaneously that the two independent variables, namely employee competency and talent management, can simultaneously influence the performance of MSME employees in the city of Bandung. The coefficient of determination also shows a value of 61.3%, which provides an explanation that the acquisition of this figure is in the very high category in explaining employee performance.